Tandem Silver‐Catalyzed Cyclization/Nucleophilic Functionalization of 2‐Alkynylindole‐3‐carbaldehyde Oximes to Afford New 2, 4‐Disubstituted γ‐Carbolines. Issue 29 (21st September 2016) - Rodrigues, Nuno; Boiaryna, Liliana; Vercouillie, Johnny; Guilloteau, Denis; Suzenet, Franck; Buron, Frederic; Routier, Sylvain
Abstract : Highly substituted pyrido[4, 3‐ b ]indole derivatives were synthesized through a straightforward one‐pot silver‐catalyzed process involving 2‐alkynylindole‐3‐carbaldehyde oximes. The tandem cyclization/nucleophilic addition sequence was optimized and applied to a wide range of nucleophiles, which reacted regioselectively at the pyrido[4, 3‐ b ]indole C4 position. The scope and limitations of the methodology were evaluated and the final compounds were obtained in fair to very good yields. This versatile method proved to be compatible with various chemical functionalities or (hetero)cycles. Abstract : A route to 2, 4‐disubstituted γ‐carbolines is reported. The reaction readily proceeds through a tandem silver‐catalyzed cyclization/nucleophilic addition sequence to afford potentially bioactive ring‐fused compounds in moderate to high yields.